ICTs and maternal healthcare utilization. Evidence from Ghana - Abekah-Nkrumah, G.; Guerriero, M.; Purohit, P. (International Journal of Social Economics, 2014)
Purpose - Traditionally, the role of technology on health services has been argued from the supply side. The purpose of this paper is to use a demand side perspective to examine the effect of Information and Communication Technologies (ICTs) on the use of maternal health services in Ghana. Design/methodology/approach - Study used data from the 2008 Ghana Demographic and Health Surveys and binary response regression models to examine the effect of women's access to ICTs on maternal healthcare utilization in Ghana. Three variables on maternal healthcare utilization were employed: use of contraception, antenatal care and place of delivery. Findings - Results from the study show that the effect of the use of technology is both positive and significant. In particular, among the other ICTs (i.e. landline phone, listening to radio, watch television, color television in household, computer in household), the coefficients of mobile phone ownership tends to be consistently significant across all four reproductive health services. Therefore, ICTs have a good capacity to influence women's demand of health information. This needs to be taken into account when designing maternal health policies and interventions. Originality/value - This is one of the few papers examining the effect of ICTs on utilization of maternal health services from the demand side compared to the popular supply side argument often found in the literature. © Emerald Group Publishing Limited.
Keywords: Demography; Development; Health policy